Evolution of Maternal Care-Associated Infections at Bogdogo University Hospital in Burkina Faso - Nana, Félicité Wendin-Manegdé; BA, Absatou; SO, Abdoulaye; Ouattara, Adama; Poda, Ghislain G; Ouedraogo, Charlemagne; Drabo, Maxime Koine (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: Healthcare-associated infections (HAIs) are major public health issues in healthcare facilities. It is one of the main causes of maternal mortality, particularly in developing countries, where infrastructure and infection control measures are often inadequate. This study aimed to determine the prevalence, most common infections, and responsible pathogens and antimicrobial resistance patterns of maternal HAIs in a healthcare facility in Burkina Faso. Methods: This retrospective cross-sectional study was based on the patients' medical records between 1 and 30 March 2025. Data from patients who developed HAIs between 2018 and 2022 were collected, with a focus on endometritis, surgical site and urinary tract infections. The causative organisms were identified, and their resistance to antimicrobials was tested. Total sampling technique was used, based on available data. Trends and factors influencing the prevalence of HAIs were also analyzed.Results: The overall prevalence of HAIs was 4.27%. The most common infections were endometritis (2.17%), urinary tract infections (1,36%), and surgical site infections (0.74%). The main pathogens identified were Enterobacteriaceae (43.3%), yeasts of the Candida genus (30.8%), and staphylococci (11%). Antimicrobial resistance was high, particularly multidrug resistance, in E. coli and K. pneumoniae strains, as well as a notable rate of methicillin-resistant Staphylococcus aureus (MRSA) at 19.04%. Conclusion: The prevalence of HAIs is high, and multidrug-resistant pathogens are a major complication. There is an urgent need to strengthen infection prevention strategies, improve microbiological surveillance, and promote rational use of antibiotics to control the spread of resistance.